Analysis of Holistic Evaluation Model Implementation in the Islamic Education Curriculum at Islamic Higher Education Institutions - Andriani, Rini Dewi; Lubis, Masruroh (Fitrah: Journal of Islamic Education, 2025)
This research departs from the problem of the less than optimal application of a comprehensive evaluation model in measuring the success of the Islamic education curriculum in Islamic universities. The existing evaluation still focuses on academic achievement, while the moral, spiritual, and character building aspects of students have not been adequately assessed. This condition causes the goal of holistic Islamic education has not been achieved as a whole. This research was conducted in three universities, namely STAI Al-Hikmah Medan, STAI Al-Hikmah Tebing Tinggi, and STIT Al-Washliyah Binjai, with the aim of analyzing the strengths and weaknesses of the implementation of the CIPP holistic evaluation model in each dimension—Context, Input, Process, and Product. The results showed that synergy between dimensions is the key to successful implementation of this model. When the context and input are strengthened and the learning process runs effectively, the educational outcomes are not only academically superior, but also shape the character and spirituality of students according to Islamic values. The implications of this research emphasize the need to develop an evaluation system that is oriented towards the balance between intellectual achievement and the formation of moral-spiritual values, so that Islamic universities are able to produce graduates with integrity, ethics, and contribute positively to society.